Miscommunication and Employee Power Dynamics May Affect Student Navigation of Library Resources / Almeida, N., & Tidal, J. (2022). Library wayfinding and ESOL students: Communication challenges and empathy-based intervention. portal: Libraries and the Academy, 22(2), 453–474. https://doi.org/10.1353/pla.2022.0025 - Bridgeman, Matthew (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2023)
Objective – To map the experiences of students of English for speakers of other languages (ESOL) navigating an academic library.Design – A wayfinding study to evaluate how students navigate a library.Setting – An urban-based academic library at an institution of higher education.Subjects – Students of English for speakers of other languages (ESOL).Methods – A mixed methods study including visual recordings, web screen capture, interviews, and surveys. Subjects were recruited through email. Twelve participants were selected and given an initial screening survey. They were given four tasks to complete: Find a book in the stacks, find a book in the reserves, find a DVD in media, and find a database. They were equipped with a GoPro camera and were given a think-aloud protocol (TAP). They were then given a post-task debriefing interview. Qualitative data were analyzed and coded. Quantitative data like success of task and time to completion were also recorded.Main Results – Success rate varied among tasks: Finding a book in reserves had the highest rate at 75%, while finding a database had the lowest at 50%. Time also varied from 12 minutes to find a book in the stacks to just under 6 minutes to find a database. Seven of the 12 participants indicated they had prior library experience; however, they still encountered skill gaps. They lacked familiarity with the space, policies, website, and terminology. Participants also struggled with library jargon and inconsistent use of jargon among staff and librarians.Conclusion – The researchers discovered there were discrepancies between language used in signs, directions provided by staff, and information provided on the website. Signage was important because several participants made remarks on lack a familiarity with the library space. They would get lost and anxious. In addition, the video recordings and subsequent discussions among the staff and librarians showed issues arising from the power dynamics in the library organization. Staff felt pressured to provide reference services when librarians were unavailable due to staffing shortages, which led to miscommunication. These conclusions lead to empathy-based training to address language discrepancies and experiences among staff. It also provided additional rationale for hiring.